2020
DOI: 10.1109/ted.2020.3007594
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Dynamic Avalanche Performance in 1.2-kV MOS-Bipolar Devices

Abstract: This is a repository copy of Evaluation of dynamic avalanche performance in 1.2kV MOSbipolar devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…However, it is found that the DA phenomenon limits the reduction of E off of conventional TIGBT and scaled TIGBTs. 9) Moreover, experimental results confirm that the DA phenomenon is enhanced at high current density operations, 9) which limits the maximum operating current density and affects the long-term reliability. 5,7) Therefore, the DA must be suppressed or eliminated when increasing the operating current density of the MOS-bipolar power switches.…”
Section: High Current Density Operationmentioning
confidence: 91%
See 1 more Smart Citation
“…However, it is found that the DA phenomenon limits the reduction of E off of conventional TIGBT and scaled TIGBTs. 9) Moreover, experimental results confirm that the DA phenomenon is enhanced at high current density operations, 9) which limits the maximum operating current density and affects the long-term reliability. 5,7) Therefore, the DA must be suppressed or eliminated when increasing the operating current density of the MOS-bipolar power switches.…”
Section: High Current Density Operationmentioning
confidence: 91%
“…[5][6][7][8] In comparison, the TCIGBTs have been experimentally evaluated to show DA free behavior and low power losses at high current density operations. [9][10][11] In addition to the onstate and turn-off behavior, the turn-on performance is also important for MOS-gated bipolar devices to achieve high switching frequency operations with low power losses.…”
Section: Introductionmentioning
confidence: 99%
“…The TCIGBT features a MOSgated thyristor structure, which consists of P-anode, N-drift, P-well and N-well. The detailed mechanisms of turn-on, selfclamping feature and PMOS actions have been explained in [10,12]. Moreover, the dummy regions are connected to the emitter, which provides a direct path for excessive holes to be evacuated during turn-off.…”
Section: Device Design and Cell Structurementioning
confidence: 99%
“…This is because DA-free operation can enable reduction in the gate resistance, reducing switching losses and enhancing reliability. The Trench Clustered IGBT (TCIGBT) is the only DA-free solution that has been experimentally proven so far [7][8][9][10][11]. Its self-clamping feature and PMOS operation are effective in managing the peak electric field distribution beneath trench gates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation